Markers for Inflammation and Oxidative Stress in Patients with Coronary Artery Disease and Microvascular Disease – Is there a Difference? - Cherneva Z. (Sciendo, 2019)
Introduction: The clinical significance of inflammation (and markers such as resistin, hsCRP) and oxidative stress (e.g. 8-isoprostanes) for microvascular disease (MVD) and coronary artery disease (CAD) is still elusive.